Ranhill SAJ Pontian Sdn Bhd / Muhammad Rizal Bainal - Bainal, Muhammad Rizal (Faculty of Business and Management, 2023)
My unforgettable and illuminating 6-month industrial training began here at Ranhill SAJ Sdn Bhd. To summaries, Ranhill SAJ Sdn Bhd is a subsidiary of Ranhill Utilities that has had a 30-year concession from the State Government to deliver treated water to Johor customers since March 2000. It also offers internships to students who want to learn about water treatment and other associated sectors such as administration, networking, and customer service. This internship report is divided into two sections, the first of which is about the organisation study in which I am participating in this industrial training. The second part concerns the investigation of observations and experiences gathered at the organisation. First and foremost, this report begins with my profile, followed by the company's profile. The company's profile, which will be presented here, comprises the establishment's past, the organization's aims and goals, as well as the organization's vision and purpose. The organisational structure is also provided to highlight the administrative system of the organisation. Aside from that, this report includes an analysis of the organization's strengths, weaknesses, opportunities, and threats (SWOT) based on my observations while receiving this training at the organisation, as well as input from my training supervisor. In order to overcome flaws and capitalise on available possibilities, the debate and recommendations to correct and improve quality are also discussed here. Every task and job that has been allocated, as well as the industrial training experience earned, is also noted here for the job and work-study. Furthermore, the training focuses on learning information and improving skills. Finally, the conclusion is the last section of my report, where I will summaries all that, I have done throughout my industrial training.